Increased circulating granzyme B in type 2 diabetes patients with low-grade systemic inflammation. (March 2019) - Cimini, Flavia Agata; D'Eliseo, Donatella; Barchetta, Ilaria; Bertoccini, Laura; Velotti, Francesca; Cavallo, Maria Gisella
Highlights: Circulating Granzyme B is increased in type 2 diabetes patients compared to non-diabetic subjects. Increased circulating Granzyme B is associated with type 2 diabetes diagnosis independently from possible confounders. Increased serum Granzyme B correlated with a systemic pro-inflammatory adipokine profile. Increased serum Granzyme B correlated with a systemic inflammatory profile linked to adipose tissue dysfunction. Abstract: In metabolic diseases, like type 2 diabetes (T2D), adipose tissue (AT) is infiltrated by macrophages and other leukocytes – which secrete many bioactive peptides leading to local and systemic low-grade chronic inflammation – and undergoes remodeling and aberrant fibrosis. Granzyme B (GrB) is a serine protease produced by some leukocytes, including cytotoxic lymphocytes and macrophages. It exerts both intracellular apoptotic function and extracellular functions, leading to tissue injury, inflammation and repair. Elevated circulating GrB levels have been found in aging- and inflammation-associated diseases and a role for GrB in the pathogenesis of several chronic inflammatory diseases has been reported. Aims of this study were to investigate circulating GrB levels in T2D patients in relation to their systemic inflammatory profile and to unravel its correlates. For this cross-sectional study, we recruited 51 consecutive T2D patients referring to our diabetes outpatient clinics (Sapienza University, Rome, Italy) for metabolic evaluations, and 29 sex, age and body mass index comparable non-diabetic subjects as control group. Study participants underwent clinical work-up; fasting blood sampling was performed for routine biochemistry and for inflammatory profile (CRP, IL-2, IL-4, IL-6, IL-8, IL-10, TNF-α, IFN-γ, GM-CSF, adiponectin, WISP1); serum GrB was measured by Human Granzyme-B Platinum Elisa kit (Affymetrix EBIO). We found that T2D patients had serum levels of GrB significantly higher than the control group (10.17 ± 12.6 vs 7.2 ± 14.1 pg/ml, p  = 0.03). Moreover, in T2D patients increased GrB correlated with unfavorable inflammatory profile, as described by elevated levels of validated adipokines such as IL-6 ( p  = 0.04), TNF-α (p  = 0.019) and WISP1 ( p  = 0.005). Furthermore, multivariate linear regression analysis showed that increased GrB was associated with T2D diagnosis independently from possible confounders. In conclusion, our results show that increased levels of circulating GrB are associated with T2D diagnosis and correlates with markers of AT-linked systemic inflammation, suggesting a potential role for GrB in the inflammatory and reactive processes occurring in metabolic diseases.